Nanocarriers-Assisted Nose-to-Brain Delivery of Levodopa: Current Progress and Prospects - Mariya Dangova; Nadezhda Ivanova; Velichka Andonova (Applied Sciences)
A challenge to contemporary medicine is still the discovery of an effective and safe therapy for symptomatic control, if not cure, of Parkinson’s disease. While the potential century’s break-through is sought and foreseen by many scientists in gene therapy, immunotherapy, new drug combinations, and neurosurgical approaches, the not-yet-conventional intranasal administration of “classic” levodopa (L-DOPA) also stands out as a perspective from which Parkinson’s patients may benefit in the short term. With the main drawbacks of the standard oral L-DOPA treatment being the extremely low systemic and cerebral bioavailability, it is widely recognized that the nasal route may turn out to be the better administration site, for it offers the alternative of direct brain delivery via the olfactory bulb (the so-called nose-to-brain axis). However, such advancement would be unthinkable without the current progress in nano-scaled drug carriers which are needed to ensure drug stability, mucosal retention and permeation, olfactory uptake, and harmlessness to the sensory neurons and respiratory cilia. This study aims to review the most significant results and achievements in the field of nano-particulate nose-to-brain delivery of L-DOPA.